THE INFLUENCE OF PRODUCT QUALITY AND HALAL LABELING ON REPURCHASE INTENTION FOR EMINA COSMETIC PRODUCTS MEDIATED BY CUSTOMER EXPERIENCE ON FEMALE STUDENTS IN BANDA ACEH CITY - Juwita, Dara; Sari, Nurma (International Journal of Kita Kreatif, 2024)
This research aims to analyze the influence of product quality and halal labeling on the intention to repurchase Emina cosmetic products which is mediated by customer experience among female students in Banda Aceh City. The data used is primary data obtained from questionnaires distributed to 105 student respondents in Banda Aceh City. This study uses a quantitative approach. The sampling method used was non-probability sampling with a technique namely purposive sampling. The analysis techniques used are path analysis and Sobel test. The results of this research show that product quality and halal labeling have a positive and significant effect on customer experience. Product quality, halal labeling and customer experience have a positive and significant effect on the intention to repurchase Emina cosmetic products among female students in Banda Aceh City. Customer experience can mediate the influence of product quality and halal labeling on the intention to repurchase Emina cosmetic products among female students in Banda Aceh City.Keyword: Product Quality, Halal Labeling, Customer Experience, Repurchase Intention